Deep intracochlear injection of triamcinolone-acetonide with an inner ear catheter in patients with residual hearing - Prenzler, Nils K.; Salcher, Rolf; Lenarz, Thomas; Gaertner, Lutz; Lesinski-Schiedat, Anke; Warnecke, Athanasia (Frontiers in Neuroscience, 2023)
Introduction In a previous study, an inner ear catheter was used to deliver low- and high-dose steroids into the cochlea prior to cochlear implant electrode insertion. With this approach, more apical regions of the cochlea could be reached and a reduction of electrode impedances in the short term was achieved in cochlear implant recipients. Whether intracochlear application of drugs via the catheter is a safe method also for patients with residual hearing has not been investigated hitherto. The aim of the present study was therefore to investigate the effect of intracochlear triamcinolone application in cochlear implant recipients with residual hearing. Patients and methods Patients with residual hearing were administered triamcinolone-acetonide (4 mg/ml; n = 10) via an inner ear catheter just prior to insertion of a MED-EL FLEX28 electrode. Impedances were measured at defined time points (intra-operatively, post-operatively and at first fitting) and retrospectively compared with a control group (no steroid application) and low- and high-dose group. Hearing thresholds were measured preoperatively, 3 days after surgery and at first fitting by pure tone audiometry. Pre- to postoperative hearing loss was determined at first fitting and compared to results from a previous study. Results The median hearing loss after implantation (125–1,500 Hz) was 20.6 dB. Four patients (40%) showed a median hearing loss of less than 15 dB, three patients (30%) between 15 and 30 dB and three patients (30%) more than 30 dB. The median hearing loss was similar to the results obtained from our previous study showing a median hearing loss of 24 dB when using FLEX28 electrode arrays. Conclusion No difference in residual hearing loss was found when comparing application of triamcinolone-acetonide using an inner ear catheter prior to the insertion of a FLEX28 electrode array to the use of the FLEX28 electrode array without the catheter. Thus, we conclude that application of drugs to the cochlea with an inner ear catheter could be a feasible approach in patients with residual hearing.